2018
DOI: 10.1007/s13205-018-1365-1
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and destruction of ants of the genus Camponotus sp. (Hymenoptera: Formicidae) in vitro by the fungus Pochonia chlamydosporia in the southeast region of Brazil

Abstract: The objective of this study was to evaluate, in vitro, the colonization and destruction of ants of the genus sp. by the ovicidal fungus (VC4 isolate), in the southeast region of Brazil. The insects used in the experiment were worker ants of the genus sp., collected periodically in the environment and immediately transported to the laboratory in test tubes. Then, VC4 growth was promoted in 2% chitin agar medium (2% WQ) to obtain a fungal solution containing conidia and/or chlamydospores. Two experimental groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Pochonia chlamydosporia is a nematophagous fungus that can alternatively parasitize eggs, belonging to the Clavicipitaceae family (Ascomycota: Pezizomycotina: Sordariomycetes: Hypocreales) (Mendoza de Gives and . Recent studies have demonstrated the possible entomopathogenic activity of this fungal species, due to its production of extracellular enzymes of the chitinase type and, with regard to this new aspects, its possible uses have been studied (Braga et al, 2013;Senna et al, 2018). However, there are no reports in the literature that mention the interaction of P. chlamydosporia on the hemiptera S. dentiventris, which can be an important step in the control of this insect pest and contribute directly to reducing the abuse of pesticides in tobacco culture.…”
Section: (With 2 Figures)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pochonia chlamydosporia is a nematophagous fungus that can alternatively parasitize eggs, belonging to the Clavicipitaceae family (Ascomycota: Pezizomycotina: Sordariomycetes: Hypocreales) (Mendoza de Gives and . Recent studies have demonstrated the possible entomopathogenic activity of this fungal species, due to its production of extracellular enzymes of the chitinase type and, with regard to this new aspects, its possible uses have been studied (Braga et al, 2013;Senna et al, 2018). However, there are no reports in the literature that mention the interaction of P. chlamydosporia on the hemiptera S. dentiventris, which can be an important step in the control of this insect pest and contribute directly to reducing the abuse of pesticides in tobacco culture.…”
Section: (With 2 Figures)mentioning
confidence: 99%
“…In the present work, a "possible" entomopathogenic activity of P. chlamydosporia on S. dendiventris eggs was observed. However, it is important to emphasize that cultivation in a rich medium on chitin, provided the conditions for chitinases production (Esteves et al, 2009;Braga et al, 2013;Soares et al, 2015;Senna et al, 2018). However, there is a scarcity of reports regarding the possible entomopathogenic activity of nematophagous fungi.…”
Section: (With 2 Figures)mentioning
confidence: 99%